Health services in an effort to control degenerative diseases in the Pakansari Cibinong sub-district - Andini, Septia; Najwa Rokhmah, Nisa; Nurmala, Sara; Fatmi, Mindiya; Ambarwati, Rini; Herlina, Nina; Nurhikmah, Wilda; Wahyuningrum, Cyntia (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2023)
Health is one of the basic human needs that is important to maintain. With good health conditions, humans can carry out activities and fulfill other life needs well. Health services are a dynamic activity in the form of helping the community in monitoring the scale of their health. Health services are efforts carried out jointly to maintain and improve health, prevent and cure disease, and increase public attention to their health conditions. Degenerative is a group of diseases in which there is a change in the function of certain parts of the body. As age increases, body function also decreases, so that degenerative diseases cannot be avoided. The dominant risk factor for degenerative diseases is heredity. Exercise habits and the habit of consuming balanced nutrition will also help with a healthy and good aging process. The aim of this service activity is so that people in the Pakansari Cibinong sub-district who take part in the activity can know the importance of knowing their health conditions and also raise awareness among the people in the Pakansari Cibinong sub-district regarding their health conditions. Activities carried out at community service events for the community in Cibinong sub-district are general health checks, Body Mass Index (BMI) checks, blood pressure checks, blood sugar checks and uric acid checks. There were 38 people who took part in the activity, including 26.3% men and 73.7% women. From the results of the examination, it was found that 39.5% of participants had a normal BMI, 47.4% were overweight and 13.2% were obese. Hypertensive conditions were found to be dominant in pre-hypertensive conditions, namely with a percentage of 29.7%. Blood sugar conditions were found to be hypertension, namely with a percentage of 86.5% and uric acid conditions were dominated by participants who had normal conditions with a percentage of 64.9%.